Effects of piracetam on Na(+)-K(+)-ATPase and monoamine oxidase in rat brain and its antioxidation effect - Qian Zeng-Nian; Gu Zheng-Lun; Jin Li-Qing; Xie Mei-Ling; Chen Bao-Quan (Acta Pharmacologica Sinica, 2016)
Piracetam, ig 600 mg.kg-1.d-1 for 30 d, caused a 20% decrease in the activity of Na(+)-K(+)-ATPase and monoamine oxidase (MAO) in vivo. In vitro, it presented an inhibitory effect on MAO, but had no direct effect on Na(+)-K(+)-ATPase at a concentration of 100 mmol.L-1. Piracetam had a potential action in scavenging free radicals. This action may be related to its clinical effects on amnesia and Alzheimer's disease.